Anticipated vs. Actual Synergy in Merger Partner Selection and Post-Merger Innovation - Rao, Vithala R.; Yu, Yu; Umashankar, Nita (Marketing Science, 2016)
Past research has primarily focused on what happens after a merger. This research attempts to determine whether anticipated benefits from the merger actually accrue. We characterize the effects of observed variables on whether pairs of firms merge, vis-à-vis roommate matching, and then link these factors to post-merger innovation (i.e., number of patents). We jointly estimate the two models using Markov Chain Monte Carlo methods with a unique panel data set of 1,979 mergers between 4,444 firms across industries and countries from 1992 to 2008. We find that similarity in national culture and technical knowledge has a positive effect on partner selection and post-merger innovation. Anticipated synergy from subindustry similarity, however, is not realized in post-merger innovation. Furthermore, some key synergy sources are unanticipated when selecting a merger partner. For example, financial synergy from higher total assets and complementarity in total assets and debt leverage as well as knowledge synergy from breadth and depth of knowledge positively influence innovation but not partner selection. Furthermore, factors that dilute synergy (e.g., higher debt levels) are unanticipated, and firms merge with firms that detract from their innovation potential. Overall, the results reveal some incongruity between anticipated and realized synergy.Data, as supplemental material, are available at https://doi.org/10.1287/mksc.2016.0978 .